2021
DOI: 10.1111/are.15111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to a therapeutic level of methylene blue on antioxidant capacity, haemato‐immunological responses and resistance of goldfish,Carassius auratustoAeromonas hydrophila

Abstract: Methylene blue (MB) can have inhibitory effects against protozoan and fungi in fish. In this investigation, fish were first exposed to different MB concentrations (0 and 2 mg L−1) for 21 days. Then, the fish were challenged with Aeromonas hydrophila for 7 days. Some haemato‐immunological and biochemical parameters, oxidative stress biomarkers in blood, growth performance and fish resistance to A. hydrophila were examined once a week. The results showed that erythrocyte, haemoglobin, leucocytes, haematocrit, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The acute toxicity of Cu, Zn and MB to fish varies based on species and life stage (Calfee et al ., 2014; Hansen et al ., 2002; Olufayo & Yusuf, 2016; Soltanian et al ., 2021; Vardy et al ., 2013; Xin et al ., 2015). For example, the LC 50 values at 96 h for copper and zinc to Puntius parrah were 0.51 and 8.46 mg l −1 , respectively; in contrast with 0.048 and 0.6 mg l −1 for Atlantic salmon ( Salmo salar ) (Ciji & Bijoy Nandan, 2014; Sprague, 1964).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute toxicity of Cu, Zn and MB to fish varies based on species and life stage (Calfee et al ., 2014; Hansen et al ., 2002; Olufayo & Yusuf, 2016; Soltanian et al ., 2021; Vardy et al ., 2013; Xin et al ., 2015). For example, the LC 50 values at 96 h for copper and zinc to Puntius parrah were 0.51 and 8.46 mg l −1 , respectively; in contrast with 0.048 and 0.6 mg l −1 for Atlantic salmon ( Salmo salar ) (Ciji & Bijoy Nandan, 2014; Sprague, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Olufayo and Yusuf (2016) assumed that MB, which is widely used as a biocide in the treatment of algae and cyanobacteria, is safe for use with fish eggs and fry for the prevention of fungal infections and was effective in reducing the bacterial load in tilapia ( Orechromis niloticus ) fingerlings (Bolivar et al ., 2012). Nonetheless, copper, zinc and MB may adversely affect various physiological processes in developing fish, resulting in higher mortality, developmental retardation, morphological and functional deformities and aberrant behaviour (Akbary et al ., 2018; Jiang et al ., 2015; Kousar & Javed, 2015; Saibu et al ., 2018; Soltanian et al ., 2021). The effects of metals on various fish organs, tissues and metabolic processes are related to osmotic disturbances and alterations in enzyme synthesis and activity (Barbara et al ., 2009; Sfakianakis et al ., 2015), which can have lethal effects on the survival of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…Perlberg et al [ 13 ] found that MB was teratogenic to Pterophyllum scalare , reporting that exposure to a 5 ppm concentration resulted in a higher incidence of non-inflatable swim bladders. In contrast, Soltanian et al [ 14 ] found that goldfish ( Carassius auratus ) exposed to a 2 mg/L solution of methylene blue for 21 days had significantly reduced lethality caused by Aeromonas hydrophila . However, the fish also exhibited significantly lower levels of neutrophils and aspartate aminotransferase, indicating some immunosuppressive effects and potential harm to their health.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, for use in water purification systems and PDT, the PSs are required to possess high solubility in water as well as efficient ISC. Methylene blue ( MB ), 9 Rose Bengal ( RB ), 10 and hydrophobically modified porphyrin derivatives 11 have been used as water-soluble PSs with high 1 O 2 Φ Δ values (0.50–0.60 for MB , 9 b,c 0.70–0.80 for RB , 9 b ,10 b and 0.50–0.60 for free base 5,10,15,20-tetrakis(4-carboxylatophenyl)porphyrin, 11 a,b respectively). Meanwhile, halogen atoms such as iodide and bromide atoms are often introduced into chromophores ( e.g.…”
Section: Introductionmentioning
confidence: 99%